Discovering Dependencies for Network Management - Bahl, Victor; Barham, Paul; Black, Richard; Chandra, Ranveer; Goldszmidt, Moises; Isaacs, Rebecca; Kandula, Srikanth; Li, Lun; MacCormick, John; Maltz, Dave; Mortier, Richard; Wawrzoniak, Mike; et al. (Workshop on Hot Topics in Networks (HotNets-V), 2006)
This paper presents the Leslie Graph, a simple yet powerful abstraction describing the complex dependencies between network, host and application components in modern networked systems. It discusses challenges in the discovery of Leslie Graphs, their uses, and describes two alternate approaches to their discovery, supported by some initial feasibility results.